2021
DOI: 10.3390/molecules26185645
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Commercial Animal and Vegetable Milks’ Lipid Profile and Its Correlation with Cell Viability and Antioxidant Activity on Human Intestinal Caco-2 Cells

Abstract: Lipids from milk are important nutritional components, although their health effects, especially for animal milks, are still questioned. Four types of commercial milks, two semi-skimmed animal milks (bovine and goat) and two vegetable ones (soy and rice), along with their total and free lipid fractions recovered by sequential centrifugation or by ethyl acetate extraction, respectively, have been analyzed. A higher antioxidant ability, reported as Trolox equivalent antioxidant capacity, was found for all raw mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…However, about the effect of LPS on the viability of macrophage, there are some different views. Some studies suggested that LPS had no significant effect on the viability of macrophages ( 50 – 54 ), some literatures mentioned that LPS could reduce the viability of macrophages ( 55 , 56 ), while other studies showed that LPS could increase the viability of macrophages ( 57 , 58 ). Consistent with the latter, our results showed that LPS could increase the viability of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…However, about the effect of LPS on the viability of macrophage, there are some different views. Some studies suggested that LPS had no significant effect on the viability of macrophages ( 50 – 54 ), some literatures mentioned that LPS could reduce the viability of macrophages ( 55 , 56 ), while other studies showed that LPS could increase the viability of macrophages ( 57 , 58 ). Consistent with the latter, our results showed that LPS could increase the viability of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid (FA) composition of PBBs is generally comprised of long-chain FAs [32]. This leads to the contribution of polyunsaturated fatty acids (PUFAs), which are beneficial for cholesterol management, i.e., low-density lipoprotein.…”
Section: Types and (Anti-)nutritional Profilesmentioning
confidence: 99%
“…1 The rational nutrient composition of plant-based milk, such as plant protein, fatty acid profile, polyphenols, and fiber, impart great physicochemical and biological properties to the final products. 2 However, many plant-based milk substitutes, especially those products based on nuts enriched with lipid content, face inescapable challenges related to their physical stability. Given the consumer demands for natural and clean label foods, finding approaches for safe and shelf-stable plant-based milk is indispensable.…”
Section: Introductionmentioning
confidence: 99%